Serology change-based clinical interpretation of indeterminate serostatus post-hepatitis B virus infection in people living with HIV - Ei Kinai; Mio Ishikura; Ryui Miyashita; Tomoko Yamaguchi; Yushi Chikasawa; Akito Ichiki; Ryoko Sekiya; Masato Bingo; Takashi Muramatsu; Mihoko Yotsumoto; Takeshi Hagiwara; Kagehiro Amano (PLoS ONE, 2025)
After hepatitis B virus (HBV) infection in people living with HIV (PLWH), various forms of indeterminate serostatuses, including “isolated anti-HBc (IAHBc)”, are observed, but the current interpretation for their HBV immunity seems to be optimistic. This single-center, retrospective cohort study of 1,461 PLWH included individuals with past natural HBV infection and negative history of HBV vaccination. Further, based on their most recent serology status, the selected individuals were classified into either 1) seroconversion, 2) chronic infection, or 3) indeterminate groups. PLWH of the latter group (with indeterminate serostatus) were defined as neither seroconversion [HBsAg(-)/anti-HBs(+)/anti-HBc(+)] nor chronic infection [HBsAg(+)/anti-HBs(-)/anti-HBc(+)]; chronological sub-serostatus of these individuals and clinical interpretations were determined based on long-term serological changes. Of the 878 PLWH with past-HBV infection and no vaccination, seroconversion was documented in 640 (73%), chronic infection in 60 (7%), and 178 (20%) were considered the indeterminate group. Based on a review of 13-year serologic tests (9 test repeats), patients of the indeterminate group were classified as either “isolated anti-HBc (IAHBc)” (n = 118, 66%), “anti-HBs alone” (n = 35, 20%), or “lost anti-HBs/anti-HBc” (n = 25, 14.0%). None showed “resolved infection” pattern. IAHBc was significantly associated with weak HBV immunity, such as viral rebound or non-seroconversion [odds ratio (OR) 2.181, 95% confidence interval (95%CI) (1.064–4.469)], while anti-HBs alone was not [OR: 0.143, 95%CI: 0.041–0.492]. Clinical interpretations of lost anti-HBs/anti-HBc were identical to those of IAHBc. In PLWH, IAHBc and lost anti-HBs/anti-HBc do not indicate resolved but weak/unstable immunity against HBV, whereas anti-HBs alone infers robust immunity.